The Application of the RADEC Learning Model to Improve the Creative Thinking Skills of Elementary School Students - Safitri, Eni; Yanuarto, Wanda Nugroho (Proceedings Series on Social Sciences & Humanities, 2025)
Creative thinking is one of the 21st century skills that students need to master in order to be able to face various personal and social problems in their lives. Creative thinking skills can be improved through the RADEC learning model. This study aims to determine the application of the RADEC learning model to improve students' creative thinking skills. The method used is pre-experiment with a one-group pretest-posttest design. The research was conducted on grade V students of SD Negeri Kutabima 04, Cimanggu District, Cilacap Regency. The sample used in the study amounted to 22 students, namely 13 males and 9 females. The instruments used were tests about creative thinking skills and observation sheets. The creative thinking ability test is carried out in two stages, namely the pretest and posttest stages. From the research, it was obtained that the average score of students' creative thinking ability in the pretest was 72 while the average posttest score was 88. The results of the study show that there is a significant difference between pretest and posttest. It can be interpreted that there is an increase in students' creative thinking skills before and after treatment using the RADEC learning model.